Kinerja Keuangan dan Tingkat Pengembalian Saham: Studi Pada Perusahaan Asuransi di Bursa Efek Indonesia - Amalia Rahmawati (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Financial Performance and Stock Return: Study at Insurance Companies Listed in The Indonesian Stock ExchangeMuch of the literature said that financial performance had an effect on the stock return, including in insurance company. The purpose of this research is to examine the effect of financial performance to stock return of insurance company that listed in Indonesia stock exchange. This research is using multiple regressions as analysis technique. The results showed that all the variables simultaneously had an effect on the stock return. By partially showed that Price Book Value, Incurred Loss Ratio, Premium Growth Ratio, and Total Asset Turnover has no significant influence on the stock return. While Return on Equity has significant positive influence on the stock return and Debt on Asset Ratio, Net Profit Margin has significant negative influence on the stock return.DOI: 10.15408/ess.v7i1.4724